Correlation of Transtibial Prosthetic Alignment Quality and Step-by-Step Variance of Gait. Issue 1 (January 2017) - Fiedler, Goeran; Johnson, Mariah Susan
ABSTRACT: Introduction: The quality of lower-limb prosthetic alignment cannot easily be measured directly but may be described by its effects on gait comfort and efficiency. It is known that gait stability and step variability are correlated, as are gait stability and prosthetic alignment. This study investigated the hypothesis that prosthetic alignment and step variability are correlated. This would have the implication that step variability can be measured to assess the quality of prosthetic alignment (and possibly other relevant factors such as prosthetic fit and componentry selection). Materials and Methods: Twelve experienced users of transtibial prostheses were subjected to a protocol that introduced malalignments of their prosthetic ankle plantarflexion angle in a randomized crossover design. Perceived alignment quality was recorded via a visual analog scale. Step-by-step variability in horizontal ground reaction forces and axial ankle torsion moment was measured using a prosthesis-integrated load cell and was statistically compared with the degree of misalignment by bivariate correlation analysis. Results: Findings suggest that variance in axial torsion moment and step duration may be correlated to alignment quality. Conclusions: Subjective patient feedback is the recommendable criterion for alignment assessment in active and experienced users of prostheses. Further research is recommended before step variance may help assess prosthetic alignment quality in patients with less experience in prosthetic use.